(untitled) (Alternautas, 2014)
One of the major tasks of the Latin American left, since the early twentieth century but especially over the past couple of decades, has been the negotiation or articulation of a political and intellectual tradition with Marxist roots and one of indigenous resistance. This post looks at the history and afterlife of a key term that has served to bridge this gap in the Bolivian context, René Zavaleta Mercado’s concept of abigarramiento or sociedad abigarrada, “motley society.” My interest in the concept is primarily as an antidote to the much-discussed slippage into a multiculturalism that is typically identified as (neo)liberal and that co-opts and neutralizes plurinational projects founded on a promise of indigenous autonomy but that can also serve a plurinationalism (and to my knowledge this connection has not received the same level of critical analysis) that operates as a discursive strategy of populist legitimation of the state.